
已知sin(π/4+2a)sin(π/4-2a)=1/6....
已知sin(π/4+2a)sin(π/4-2a)=1/6,a∈(π/4,π/2)(1)求cos4a的值(2)求2根3sin^2a+tana-cota-根3的值...
已知sin(π/4+2a)sin(π/4-2a)=1/6,a∈(π/4,π/2)
(1)求cos4a的值
(2)求2根3sin^2a+tana-cota-根3的值 展开
(1)求cos4a的值
(2)求2根3sin^2a+tana-cota-根3的值 展开
1个回答
展开全部
sin(π/4+2A)sin(π/4-2A)
=[cos4A-cos(π/2)]/2
=(cos4A)/2=1/6
故cos4A=1/3,
而A∈(π/4,π/2),2A∈(π/2,π),4A∈(π,2π)
cos4A=2cos^2 2A-1
1/3=2cos^2 2A-1
2cos^2 2A=4/3
cos^2 2A=2/3
cos2A=-√6/3
sin^2 2A=1/3
sin2A=√3/3
2√3sin^2 A+tanA-cotA-√3
=√3(2sin^2 A-1)+(sin^2 A-cos^2 A)/sinAcosA
=-√3cos2A+(sin^2 A-cos^2 A)/sinAcosA
=-√3cos2A-2cos2A/sin2A
=√3cos2A(1-2/sin2A)
=√3(-√6/3)[1-2/(√3/3)]
=-√2[1-2√3]
=2√6-2
=[cos4A-cos(π/2)]/2
=(cos4A)/2=1/6
故cos4A=1/3,
而A∈(π/4,π/2),2A∈(π/2,π),4A∈(π,2π)
cos4A=2cos^2 2A-1
1/3=2cos^2 2A-1
2cos^2 2A=4/3
cos^2 2A=2/3
cos2A=-√6/3
sin^2 2A=1/3
sin2A=√3/3
2√3sin^2 A+tanA-cotA-√3
=√3(2sin^2 A-1)+(sin^2 A-cos^2 A)/sinAcosA
=-√3cos2A+(sin^2 A-cos^2 A)/sinAcosA
=-√3cos2A-2cos2A/sin2A
=√3cos2A(1-2/sin2A)
=√3(-√6/3)[1-2/(√3/3)]
=-√2[1-2√3]
=2√6-2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询